Tecnologie di monitoraggio per l'emergenza SARS Cov-2 (GEOmedia, 2020)
3D Target is a company that for more than 10 years has specialized in providing solutions in the field of non-contact measuring instruments, exactly what everyone, people and companies, need today to work safely and interact with other people.In this regard, also on the basis of the contacts made in this period with its customers and suppliers, 3D Target has identified some products to help people and companies to face this some products to help.